Effects Of Van Hiele’s Phase-Based Teaching Strategy And Gender On Pre-Service Mathematics Teachers’ Geometry Achievement And Attitude Towards Geometry In Niger State, Nigeria - Usman, Hassan (2019)
The study investigated the effects of van Hiele’s phase-based teaching strategy and gender on pre-service mathematics teachers’ geometry achievement and attitude towards geometry in Niger State, Nigeria. Six research questions and corresponding hypotheses were formulated to guide the study. The research design adopted for the study was a two-by-two (2x2) quasi experimental factorial design. One hundred and forty-nine (149) pre-service mathematics teachers from two colleges of education situated in Niger state were used as research sample. The sample colleges were selected using a purposive sampling technique. The experimental group was exposed to van Hiele’s phase-based teaching strategy while the control group was taught same topics with conventional teaching strategy. Geometry Achievement Test (GAT), is a 30 – item test covering topics in Geometry was used to collect data for both pre and post achievement test, while Attitude Towards Geometry Questionnaire (ATGQ) was used for collecting data on attitude towards geometry. A reliability coefficient of 0.78 and 0.73 was respectively obtained for Geometry Achievement Test and Attitude Towards Geometry questionnaire. The data were analyzed using two-way analysis of variance (ANOVA) and Analysis of Covariance (ANCOVA). The hypotheses were tested at 0.05 level of significance.